Magie der Zahl in der Kunst des 20. Jahrhunderts. - Bill, Max; Bochner, Mel; Conzen, Ina; Guderian, Dietmar; Heinlein, Stefan; von Holst, Christian; von Maur, Karin; Mields, Rune; Molzahn, Johannes; de la Motte-Haber, Helga; Opalka, Roman; Peignot, Jérôme; et al. (Stuttgart : Staatsgalerie Stuttgart, 1997)
Alfano, Carlo ; Andre, Carl ; Antes, Horst ; Arends, Stuart ; Arman ; Art & Language ; Bäcker, Heimrad ; Balla, Giacomo ; Barcelo, Miquel ; Barradas, Rafael ; Barroso, Cristina ; Basquiat, Jean-Michel ; Baumeister, Willi ; Bayer, Herbert ; Beckley, Bill ; Bernhardt, Ulrich ; Bert, Lore ; Bertini, Gianni ; Beuys, Joseph ; Bickerton, Ashley ; Bill, Max ; Blum, Heiner ; Blumenfeld, Erwin ; Boccioni, Umberto ; Bochner, Mel ; Boetti, Alighiero ; Bogner, F. J. ; Borofsky, Jonathan ; Braque, Georges ; Brecht, George ; Brodwolf, Jürgen ; Broodthaers, Marcel ; Brouwn, Stanley ; Burckhardt, Klaus ; Büttner, Werner ; Byron, Michael ; Cage, John ; Cangiullo, Francesco ; Caris, Gerard ; Carnwath, Squeak ; Carrà, Carlo ; Chevalier, Miguel ; Chlebnikov, Velimir ; Clemente, Francesco ; Closky, Claude ; Cohen, Elaine Lustig ; Copley, William ; Crotti, Jean ; Dali, Salvador ; Darboven, Hanne ; Defraoui, Silvie & Cherif ; Degas, Edgar ; Delaunay, Robert ; Demuth, Charles ; Denes, Agnes ; Depero, Fortunato ; Dias, Antonio ; van Doesburg, Theo ; Dossi, Ugo ; Droese, Felix ; Duchamp, Marcel ; Dürer, Albrecht ; Edzgveradze, Gia ; Ermilov, Vasilij ; Ernst, Max ; van Eyck, Jan ; Felixmüller, Conrad ; Ferrer, Esther ; Fibonacci, Leonardo ; Filliou, Robert ; Flatz, Wolfgang ; Freyburg, Carl von ; Fulton, Hamish ; Gabo, Naum ; Gaines, Charles ; Galadshev, Pyotr S. ; Gappmayr, Heinz ; Garnier, Ilse & Pierre ; Geiger, Rupprecht ; Genkinger, Fritz ; Gerdes, Ludger ; Giers, Walter ; Giese, Imi ; Gijsbrechts, Cornelis Norbertus ; Goller, Bruno ; Gosewitz, Ludwig ; Gostomski, Zbigniew ; Graham, Dan ; Gris, Juan ; Gross, Sabine ; Grosz, George ; Grunow, Gertrud ; Haagmans, Fons ; Halfa, Detlef ; Harnett, William M. ; Hartley, Marsden ; Hausmann, Raoul ; Heartfield, John ; Heider, Klaus ; etc.
Magie der Zahl in der Kunst des 20. Jahrhunderts, Staatsgalerie Stuttgart, 1. Februar bis 19. Mai 1997
Duits
boek